Structural and functional insights into the role of Carbohydrate Esterases and Carbohydrate-Binding Modules in plant cell wall hydrolysis - Correia, Marcia Alexandra da Silva (2010)
Tese de Doutoramento em Ciência e Tecnologia Animal